Significant Immunohistochemical Expression of Human Chorionic Gonadotropin in High-Grade Osteosarcoma is Rare, but May Be Associated with Clinically Elevated Serum Levels. (July 2014) - Lee, Anna F.; Pawel, Bruce R.; Sullivan, Lisa M.
Survival rates have plateaued at 70% for osteosarcoma. Proteins ectopically produced by malignant tumors may provide insight into new therapeutic targets. Osteosarcomas secreting human chorionic gonadotropin (hCG) have been suggested to have a worse prognosis. We examined the frequency of expression of β-subunit of hCG (β-hCG) in pretreatment osteosarcoma biopsies, and asked if it was associated with various clinical prognostic parameters, and the development of metastases. We subjected 51 pretreatment biopsies of high-grade osteosarcoma, from 51 patients, to β-hCG immunohistochemistry. In 19 of these patients, postchemotherapy metastatic biopsies also were examined for β-hCG expression. Clinical information (patient age, sex, survival status, and serum hCG in females only), and tumor characteristics (site, size, and presence of metastases) were recorded. The β-hCG positive and negative biopsies were separated and compared. Of 49 interpretable pretreatment biopsies, 28 (57%) showed positive cytoplasmic β-hCG expression: 27 with sparse positivity (1% of tumor cells) and 1 with frequent positivity (10% of tumor cells). The patient with frequent β-hCG positivity in her pretreatment biopsy had elevated serum hCG (88.2 mIU/mL) at diagnosis, decreasing to undetectable following chemotherapy and definitive resection. There was no difference in clinical parameters or rate of metastasis between β-hCG positive versus negative groups. Expression of β-hCG may be seen in high-grade osteosarcoma, but frequent β-hCG immunohistochemical expression by tumor cells, associated with clinically elevated serum β-hCG, is rare. Recognition that some nongerm cell tumors may produce β-hCG can prevent confusion with malignancies containing neoplastic syncytiotrophoblast cells, including germ cell and trophoblastic tumors.